Critical and Creative Thinking Skills of Pekanbaru High School Students in Biology Learning - Idris Tengku (Postgraduate, University of Mataram, 2022)
Critical and creative thinking are skills that are needed in this 21st century. These two skills are a priority for learning outcomes from various levels of education. This research is a descriptive study that aims to see or measure the critical and creative thinking skills of high school students in Pekanbaru in online learning. The population in this study were students of public senior high school class XI IPA in Pekanbaru, while the sample was 216 students from two public senior high schools in Pekanbaru. The research instrument is in the form of critical and creative thinking questions that have been validated constructively by experts and empirically with a reliability value of. Based on the results of the study, it shows that the critical thinking skill of students of public senior high school class XI IPA in Pekanbaru is in the sufficient category with a percentage of 68.71% with the highest percentage being in the advance clarification indicator with a very good category while the other indicators are in the sufficient category. In creative thinking, the average skill of students in public senior high school class XI IPA in Pekanbaru is also in the sufficient category with a percentage of 64.43% with all indicators in the sufficient category. Based on the results of the study, it can be concluded that the ability of students in public senior high school class XI IPA at SMAN Pekanbaru is in a fairly good category.